Hypocobalamin in a Dog - Hematological Changes - Saynovich Dutra Silveira, Nathalia (2024)
Background: Cyanocobalamin is a water-soluble vitamin found mainly in foods of animal origin and is essential for synthesizing proteins, neurotransmitters and nucleic acid. Changes in the metabolism of this vitamin leading to hypocobalaminemia or deficiency are observed in gastrointestinal disorders or hereditary defects resulting in hematological, neurological or metabolic manifestations. This work aims to report the hematological changes resulting from hypocobalaminemia in a canine, diagnosed through the measurement of vitamin B12, folic acid and changes observed in the blood count and myelogram. Case: A 5-year-old castrated male mixed breed dog, weighing 8.30 kg, was treated, with history of main complaint being halitosis and the presence of dental calculus, in addition to difficulty chewing and sporadic vomiting after exercise. In the hematological evaluation, metarubricytosis, the presence of megaloblastic rubrics, leukopenia due to neutropenia, hypersegmented neutrophils and erythrocyte morphological changes were demonstrated in the evaluation of the blood smear, such as macrocytosis with nuclear fragmentation, Cabot rings, basophilic stippling and siderotic inclusions. No changes were found in serum biochemistry, measurement of clotting times, and ultrasound evaluation. The parasitological examination of feces showed cysts of Giardia spp. Vitamin B12 and folic acid were measured, which revealed hypocobalaminemia and hyperfolatemia, and a new blood count and myelogram were subsequently performed, which showed normochromic macrocytic anemia (megaloblastic), erythroid hyperplasia with an increase in precursors and prominent dysplasia (dyserythropoiesis), in addition to mild dysgranulopoiesis and dysmegakaryocytopoiesis, with a suggestive diagnosis of Myelodysplastic Syndrome with Refractory Cytopenia of Multiple Lineages. The main dysplastic changes observed in the erythroid lineage were megaloblastic erythrocytes, multilobulated, nuclear fragmentation, asynchrony in nuclear and cytoplasmic maturation, presence of occasional siderotic inclusions and abnormalities in nuclear chromatin, in addition to typical and atypical mitotic figures, which are consistent with the findings observed in the blood count. As a treatment, the administration of vitamin B12 was prescribed parenterally; however, the owner did not return for treatment. Discussion: The changes observed in the blood count, such as macrocytosis, the presence of megaloblastic rubrics and those observed in the myelogram, are compatible with megaloblastic anemia resulting from hypocobalaminemia and corroborate the findings in humans but have not been well elucidated in animals to date. Nutritional deficiency of vitamin B12 can lead to hematological changes due to myelodysplasia similar to those observed in myelodysplastic syndromes, making it essential to differentiate between the two conditions. Among the causes of hypocobalaminemia, intestinal dysbiosis seems to be the most likely cause, with concomitant hyperfolatemia also observed. In conclusion, this report reinforces the importance of carrying out laboratory tests within Veterinary Medicine, as it provides highly relevant information for the early diagnosis of diseases that often do not present evident clinical signs, in addition to the hematological findings of hypocobalaminemia reported. They contribute from a scientific point of view because, to date, they have not yet been well described for the canine species, contrary to what is observed in humans. Keywords: cabot ring, megaloblastic anemia, vitamin B12 deficiency, hyperfolatemia, siderotic inclusions, myelodysplastic syndrome. Título: Hipocobalaminemia em cão - alterações hematológicas Descritores: anel de cabot, anemia megaloblástica, deficiência de vitamina B12, hiperfolatemia, inclusões sideróticas, syndrome mielodisplásica.